BUILDING ENVIRONMENT FOR INNOVATIVE START-UPS IN THE CZECH REPUBLIC - Štochlová, Karolina (2012)
The goal of this thesis is to identify the challenges and success factors of the support system for innovative start-ups in the Czech Republic as well as to formulate recommendations for the implementation of the currently envisaged Seed fund project. The thesis covers the specifics of start-up companies and barriers for their development and puts them in relation with the current state of the Czech entrepreneurial environment and its innovation performance. Hard data as well as opinions of experts and potential investors are assessed to analyze the needs and motivations of both demand and supply sides of the venture capital market in order to provide some valuable insights which may help the support system to improve the access of entrepreneurs to external finance and boost the creation of innovative start-ups in the Czech Republic. The main suggestions introduced relate to the focus on retaining strict transparency, to the careful selection of entities evaluating the viability of projects and those providing services assisting the entrepreneurs in the preparation phase. Finally, the right setting of conditions of the Seed fund to attract both private investors and entrepreneurs will determine the success of the whole project.